Abolition of poverty in India: with special reference to target group approach in Gujarat - Hirway, Indira (New Delhi, 1986)
This study of Target Group Approach of Poverty Eradication deserves special attention of planners and social scientists. The unique feature of the study is that it analyses a set of target group programmes within the context of the actual functioning of four different types of villages, taking into account the economic structure. the social framework and power alignments of these village societies. It shows how these special programmes, instead of loosening the hold of the power structure, strengthen it in myriad ways and how they deprive the poor of the benefits of even those programmes which are specially designed for them. The book points out that the target group approach is not likely to deliver goods and radical changes in the approach are called for.
Keywords: Poverty